THE IMPORTANCE AND CHALLENGES OF OUTCOME-BASED EDUCATION â€" A CASE STUDY IN A PRIVATE HIGHER EDUCATION INSTITUTION - Poi Hun Sun; Sek Yan Lee (UUM Press, 2020)
Purpose â€" Given the importance of quality assurance and enhancement of curriculum in a higher education institution, it is vital to have a systematic process to measure studentsâ€™ performance objectively and effectively for continuous improvement in the programme/curriculum. The purpose of this study is to analyse the process of setting up an Outcome-Based Education (OBE) system in a business school of a private higher education institution in Malaysia. The importance and challenges of the OBE system are discussed, while some recommendations for common issues are suggested.   Methodology â€" Document analyses and observations were conducted on ten undergraduate programmes in the business school of a private higher education institution, from 2015 to 2019. These mechanisms are to assess and discuss the processes needed in implementing OBE; while the importance and challenges of having an OBE system in the business school are included.   Findings â€" To have a smooth-running process of implementing an OBE system, proper planning needs to be in place. Data from the OBE system and its utilisation are essential to ensure continuous quality improvement to the curriculum and to give assurance to relevant stakeholders about the quality of graduates. There are several steps that are discussed in this paper to give pointers and guidance to other education institutions in setting up of the OBE process. However, it is undeniable that investment of time and effort is needed to ensure the smooth-running of the OBE establishment and maintenance.   Significance â€" This study is essential to provide a guideline to relevant parties in setting up an OBE system in education institutions. An OBE system is needed to measure studentsâ€™ performance objectively and effectively while enriching studentsâ€™ learning experiences. This study will give pointers to the management of the education institution, policy makers, accrediting bodies and academics on implementing an OBE system in the education institutions.